Challenges - Senathirajah, Pathman; VStudios ([S.l.] : VStudios, 2008)
In the networking business, it would seems that cards are stacked up against you from the very beginning. Walls of every shape, size and color spring up your goals and your dreams. Pathman Senathirajah dares you to take a look into your own heart and discover for yourself the warrior within
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing